2021
DOI: 10.1002/hbm.25561
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear manifold learning in functional magnetic resonance imaging uncovers a low‐dimensional space of brain dynamics

Abstract: Large‐scale brain dynamics are believed to lie in a latent, low‐dimensional space. Typically, the embeddings of brain scans are derived independently from different cognitive tasks or resting‐state data, ignoring a potentially large—and shared—portion of this space. Here, we establish that a shared, robust, and interpretable low‐dimensional space of brain dynamics can be recovered from a rich repertoire of task‐based functional magnetic resonance imaging (fMRI) data. This occurs when relying on nonlinear appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 51 publications
(81 reference statements)
3
42
0
Order By: Relevance
“…In fact, increasing evidence suggests that key observable facets of brain processes operate in a low dimensional space ( 21 ). At the neuronal level, complex interactions between brain areas underlie emergent population-level properties that cannot be captured at the level of individual neurons; similar observations are becoming prevalent in neuroimaging ( 22 ). Notably, this substantial low dimensional structure is expected to account for the unmatched performance of the sole multivariate method tested here and in related recent work ( 14 ).…”
Section: Discussionmentioning
confidence: 71%
“…In fact, increasing evidence suggests that key observable facets of brain processes operate in a low dimensional space ( 21 ). At the neuronal level, complex interactions between brain areas underlie emergent population-level properties that cannot be captured at the level of individual neurons; similar observations are becoming prevalent in neuroimaging ( 22 ). Notably, this substantial low dimensional structure is expected to account for the unmatched performance of the sole multivariate method tested here and in related recent work ( 14 ).…”
Section: Discussionmentioning
confidence: 71%
“…We iteratively searched for the optimal number of states (K), within a range of 2-8. K was determined based on the model's consistency (Vidaurre et al, 2018) and clustering performance (Calinski and Harabasz, 1974;Gao et al, 2021). We first tested the model consistency across iterations, where the same HMM training and inference procedures were repeated 5 times using the same hyperparameters.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, embedding the resting state data onto the task manifold extracted with the help of diffusion maps (Gao et al, 2021) found the resting state time-points concentrate in the task-fixation and transition subspaces complemented by a minority of time points in the cognitive subspaces of the manifold.…”
Section: Discussionmentioning
confidence: 99%